2022
DOI: 10.3390/jcm11144055
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Appraisal of Intravascular Ultrasound and Optical Coherence Tomography in Invasive Coronary Imaging: 2022 Update

Abstract: Although coronary angiography has been well established as a standard modality for percutaneous coronary intervention guidance, recent developments in intravascular imaging techniques, such as intravascular ultrasound and optical coherence tomography, have become increasingly adopted, enabling direct detailed lesion visualization, including lesions beyond the scope of assessment using exclusively angiography. Intravascular imaging modalities have been reported to potentially improve both short- and long-term p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 59 publications
0
12
0
Order By: Relevance
“…Coronary artery calcifications (CAC) have a strong negative impact on the clinical outcomes of percutaneous coronary intervention (PCI). The prevalence of CAC is relatively high and reaches up to 40% when the diagnosis is made based on angiographic assessment and even up to 70% when intravascular ultrasound (IVUS) is used [1,2]. Adequate lesion preparation before drug-eluting stent (DES) implantation is a crucial point of the PCI procedure to achieve satisfying results.…”
Section: Introductionmentioning
confidence: 99%
“…Coronary artery calcifications (CAC) have a strong negative impact on the clinical outcomes of percutaneous coronary intervention (PCI). The prevalence of CAC is relatively high and reaches up to 40% when the diagnosis is made based on angiographic assessment and even up to 70% when intravascular ultrasound (IVUS) is used [1,2]. Adequate lesion preparation before drug-eluting stent (DES) implantation is a crucial point of the PCI procedure to achieve satisfying results.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, the procedures have scarcely been introduced in clinical practice and have still managed to obtain bail-out life-saving status in extremely high-risk patients. Moreover, for the same reason, the rate of intravascular guidance has been comparatively low [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…These measurements have been found to correlate reliably with coronary physiological measurements such as instantaneous free-wave ratio (iFR), fractional flow reserve (FFR), and non-invasive stress testing representing ischemic lesions in the right clinical setting [49][50][51] . The studies showed that (Adapted from Baruś et al [45] under Creative Commons License). FD-OCT: frequency domain optical coherence tomography; IVUS: intravascular ultrasound; MLA: minimal lumen area; OCT: optical coherence tomography.…”
Section: Current Use Of Intravasculr Imaging In Percutaneous Coronary...mentioning
confidence: 99%
“…A, The MLA was 2.75 mm 2 by OCT; B, The MLA was 3.50 mm 2 by IVUS; C, The planar reconstruction of the vessel morphology by OCT; D, The planar reconstruction of the vessel morphology by IVUS. (Adapted from Baruś et al[45] under Creative Commons License). FD-OCT: frequency domain optical coherence tomography; IVUS: intravascular ultrasound; MLA: minimal lumen area; OCT: optical coherence tomography.…”
mentioning
confidence: 99%